Relationship between maternal scaffolding and preschooler's metacognitive strategies in a problem-solving situation - Stern, Maren; Hertel, Silke (Learning and instruction, 2022)
This study examined how mothers' scaffolding predicts preschoolers' metacognitive strategies and task performance. N = 132 preschoolers and their mothers participated in the study. Problem-solving tasks were solved in mother-child interactions and independently. Mothers' scaffolding (means; cognitive, metacognitive, autonomy support) and mother-child task performance were coded during mother-child interactions. Children's metacognitive strategies and task performance were coded during child-alone problem-solving. Path-model analyses found that mothers' metacognitive support was negatively - and autonomy support positively - associated with mother-child task performance. Mothers' scaffolding means served different scaffolding intentions, building two scaffolding strategies: (1) Mothers using more scaffolding means provided more cognitive support, which was related to lower levels of children's metacognitive strategies. (2) Mothers using fewer scaffolding means provided more autonomy support, which was related to higher levels of children's metacognitive strategies. This study demonstrates the importance of examining scaffolding strategies and shows that different scaffolding strategies may be relevant in joint and child-alone problem-solving.
Online veröffentlicht: 24. Mai 2022
Gesehen am 13.07.2022